Organization of the Operating Environment for Industrial Robots Processing Flat Objects That Have Asymmetry of Part Surfaces - KARMALITA, A.; PUNDYK, S.; ONOFRIICHUK, V.; SMUTKO, S.; SHPAK, O.; HORIASHCHENKO, S.; BILYI, L. (Science and Innovation, 2024)
Introduction. Orientation of fl at parts with asymmetry of their surface properties is a necessary condition for the use of industrial robots to feed these parts for machining. Problem Statement. After each machining operation, the parts may be found in a disordered state, therefore, in order feed them for the next operation, it is necessary to control their position and properly reorient them. Purpose. The purpose of this research is to experimentally determine the coeffi cient of asymmetry of topographic properties of surfaces for controlling the position of fl at parts by the air jet method. Material and Methods. The method of determining the speed of air by measuring the pressure in it, with the help of a Pitot-Prandtl tube, has been used. The standard MathCad package has been employed for mathematical calculations of experimental results. Sheet steel for the manufacture of air chambers and fl uoroplastic with high anti-friction properties have been used as material for the experimental stand for the base. Results. As a result of experimental studies, a list of the parts for which the control method using air jets has high reliability has been formed. Through research, the coeffi cient c has been established for parts made of diff erent materials. This coeffi cient aff ects the regularity of the motion of parts, and knowing it we may calculate the necessary parameters of devices for control. The necessary air pressure to create a force suffi cient to move these parts from the control position at a given speed, that is, to create control conditions has been established. Conclusions. The use of compressed air to control the position of fl at parts with asymmetric surfaces can be successfully implemented for organizing the operating environment of industrial robots that work according to a rigid algorithm, with the help of pneumatic devices, the parameters of which can be determined based on the results of this research, or for creating sensor grippers for adaptive industrial robots.